MULTIPLE MYELOMA WITH CENTRAL NERVOUS SYSTEM INVOLVEMENT – CASE SERIES - Kojić, Andrijana; Purić, Mila (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Central nervous system involvement in multiple myeloma (CNS-MM) is a very rare entity accounting for less than 1% of all extramedullary multiple myeloma, which manifests as a variety of neurological deficits. Treatment modalities can be locally administered therapy, including intrathecal chemotherapy and radiotherapy, as well as systemic therapy, including autologous/allogeneic hematopoietic stem cell transplantation (AHSCT). The aim: This article aims to present the experience of our center in the treatment of this rare entity. Case reports: The first patient was diagnosed with multiple myeloma BJ lambda CS IIIA R-ISS 2 with a tumor mass located at the base of the skull, causing right facial nerve paralysis. The patient underwent six treatment cycles of the CVD (cyclophosphamide, bortezomib, dexamethasone) regimen, achieving partial remission, followed by palliative radiation and autologous stem cell transplantation. The treatment was continued with the DaraRd (daratumumab, lenalidomide, dexamethasone) regimen aimed at a second stem cell transplant which is to be carried out upon deepening remission. The overall survival of the patient, so far, is 20 months. The second patient with multiple myeloma BJ kappa CS IIIA ISS 2 developed CNS involvement with the first recurrence of the disease. Cranial radiation and seven cycles of the PAD (bortezomib, doxorubicin, dexamethasone) regimen were carried out, leading to disease progression and death. The overall survival of the patient was 48 months, with 25 months survival since the diagnosis of CNS infiltration. Conclusion: Despite advances in diagnosis and treatment, the prognosis for CNS-MM remains poor because of its complex and aggressive clinical behavior. Due to its low incidence, available data are limited indicating the need for further studies involving this small group of patients.